A Novel Drive Option for Piezoelectric Ultrasonic Transducers. (21st July 2011) - Engelke, Diana; Oehme, Bernd; Strackeljan, Jens
Abstract : This paper concentrates on ultrasonic transducers, which are driven by piezoelectric ceramic rings that are arranged in a stack. A novel drive option, where the stack contains a new type of divided piezoelectric rings, is analyzed using the finite element method, prototyped, and tested. To gain a better sense of the vibration behavior, the studies focus initially on one ring and subsequently on the different possibilities to assemble the transducer. The investigations point out that natural bending frequencies can be excited at the transducer. Thus, multiple vibration directions of the tip can be controlled, what can be advantageous for instance in dental applications.